Request Extraction in Magpie: Events, Schemas, and Temporal Joins - Isaacs, Rebecca; Barham, Paul; Bulpin, James; Mortier, Richard; Narayanan, Dushyanth (Proceedings of ACM SIGOPS European Workshop (SIGOPS EW'04), 2004)
This paper addresses the problem of extracting individual request activity from interleaved event traces. We present a new technique for event correlation which applies a form of temporal join over timestamped, parameterized event streams in order to identify the events pertaining to an individual request. Event schemas ensure that the request extraction mechanism applies to any server application or service without modification, and is robust against future changes in application behavior. This work is part of the Magpie project [2], which is developing infrastructure to track requests end-to-end in a distributed system.